Peer Support in Forming Self Esteem in the Millennial Era - Fany Rifqoh; Moh. Farozin; Budi Astuti (Yayasan Insan Mulia Bima, 2024)
The millennial generation is a generation of the 21st century whose presence is often called the Gen-Z generation. Psychology is the main difference between this generation and other generations. Factors that support them to remain enthusiastic in learning need to be implemented. In line with this. This research aims to describe survey results related to social support from peers in shaping self-esteem for the millennial generation. This research is a descriptive survey research. The main data sources are observation, interviews and questionnaires. The research steps taken were analyzing the data and validating the data with expert opinions, as well as several relevant studies. The research respondents were class X students at MA Sunan Pandanaran Yogyakarta. The research results show that. Peer support that has been carried out by MA Sunan Pandanaran students is social emotional support; award information. And instrumental. Based on the results of interviews and filling out questionnaires, several forms of social support from peers are considered to be able to increase self-esteem for students.